Cue reactivity and opioid blockade in amphetamine dependence: A randomized, controlled fMRI study. (1st October 2018) - Guterstam, Joar; Jayaram-Lindström, Nitya; Berrebi, Jonathan; Petrovic, Predrag; Ingvar, Martin; Fransson, Peter; Franck, Johan
Highlights: Drug-related films cause strong craving in amphetamine (AMP) dependent patients. Drug cue exposure activates motivational and attentional networks in the brain. Naltrexone does not seem to affect drug cue reactivity in AMP dependence. Abstract: Background: The opioid antagonist, naltrexone, has been shown to reduce the risk of relapse in amphetamine dependence, but the mechanisms behind this effect are not well understood. We aimed to investigate if naltrexone attenuates cue reactivity and craving in amphetamine dependence. Methods: Forty men with severe, intravenous amphetamine dependence were randomized to one dose of naltrexone (50 mg) or placebo. In a BOLD fMRI cue reactivity paradigm, they were exposed to drug-related and neutral films and gave subjective ratings of craving after each film. Twenty-nine patients left data of sufficient quality to be included in the final analysis. Results: The drug-related films elicited strong subjective craving and BOLD activations of the striatum, cingulate cortex, and occipito-temporal visual attention networks. Longer history of amphetamine use was associated with greater activations of the prefrontal cortex. Naltrexone as compared to placebo had no significant effects on brain activations or subjective ratings. Conclusion: Patients with severe stimulant use disorder exhibit strong neural cue reactivity, the patterns of which are modulated by duration of drug use. In this sample, we found no evidence for any effects of naltrexone on cue reactivity.